(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Ehlers–Danlos syndrome (EDS) is a rare disease characterized by connective tissue dysplasia, and, consequently, structural changes in ocular tissues. To the best of our knowledge, only 3 cases of surgical treatment with vitrectomy for retinal detachment in EDS have been reported in the literature. Purpose: To review an approach to medical and surgical treatment for recurrent retinal detachment in a patient with EDS. Material and Methods: Data on the clinical condition of eyes, examination findings and outcomes of conservative and surgical treatment were reported. Results: Substantial remnants of the vitreous were found in the periphery during surgical re-examination of the vitreous cavity, and were as much as possible removed with a vitreous cutter. Trypan blue staining of the retina facilitated the removal of the epiretinal membrane covering the whole posterior pole, and the membrane was completely removed with forceps. Conclusion: We argue for a more differentiated approach to the examination and treatment of patients with Ehlers–Danlos syndrome, because connective tissue dysplasia may mimic another systemic autoimmune disease. Early treatment and adequate treatment strategy enable treatment success for especially severe cases.